Socio-economic status scales updated for 2017 - Singh, Tulika; Sharma, Sanju; Nagesh, Seetharamaiya (International Journal of Research in Medical Sciences, 2017)
The health status of any country depends on the socio-economic status (SES) and the per capita income of its citizens. The SES also decides the affordability and utilization of the health facilities. Constant changes in the price of goods in the country due to inflation make it mandatory to constantly update the income-based socioeconomic scales. This paper attempts to provide updates in Kuppuswamy, B.G. Prasad and udai pareek socioeconomic scales for 2017.